An investigation of factors supporting the psychological health of staff in a UK emergency department. Issue 7 (27th June 2011) - Yates, Philip J; Benson, Elizabeth V; Harris, Adrian; Baron, Rachel
Abstract : Study objective: Research indicates emergency department doctors experience high levels of stress. Poor psychological health affects staff well-being and patient care, with considerable organisational and financial cost. This study compares levels of psychological health in medical, nursing and administrative staff from a UK emergency department with an orthopaedic comparison department. The study investigates the influence of coping strategies and the support people receive from their colleagues (ie, social support). Methods: Comparative design, using self-report questionnaires comparing emergency (n=73) and orthopaedic (n=63) staff. Measures included: General Health Questionnaire-12, Hospital Anxiety and Depression Scale, Brief COPE, and questions relating to social identity and social support. Results: The proportion of staff experiencing clinically significant levels of distress was higher than would be expected in the general population. The increased risk of psychological distress previously shown for emergency doctors is not present here for other emergency staff members. Better psychological health was associated with greater use of problem-focused coping and less use of maladaptive coping. Social support was associated with better psychological health and greater use of problem-focused coping. Conclusions: Priority should be given to developing and evaluating interventions to improve psychological health for this group. Findings suggest that coping strategies and social support are important factors to incorporate into such interventions.